Analyzing the WISC-R in children with ADHD: The predictive value of subtests, Kaufman, and Bannatyne categories - Tural, Hesapçioğlu S.; Çelik, C.; Özmen, S.; Yiğit, I. (Turkish Association of Nervous and Mental Health, 2016)
Objective: The aim of this study was to evaluate the predictive value of Intelligence Quotient scores (IQs), subtests of Wechsler Intelligence Scale for Children-Revised (WISC-R), and the Kaufman's and Bannatyne's categories scores in attention deficit hyperactivity disorder (ADHD). In addition, this study was designed to examine the difference of some neurocognitive skills for children with ADHD and their unaffected peers using the WISC-R subtests. Method: WISC-R's subtest and IQ scores, and scores of Kaufman's and Bannatyne's categories of the children who were diagnosed with only ADHD were compared with the same scores of the children in the healthy control group (N= 111) and the ADHD with comorbid group (N= 82). Results: It was found that the subtest scores (vocabulary, comprehension, digit span, picture completion, and block design) of the children with only ADHD and ADHD with comorbidity were significantly lower than the healthy group. In addition, object assembly subtest scores of the children with only ADHD were lower than the control group. Subtests of comprehension (Wald = 5.47, df = 1, p=0.05), digit span (Wald = 16.79, df = 1, p=0.001), and picture completion (Wald= 5.25, df= 1, p=0.05) were able to predict ADHD significantly. In this study, the categories of freedom from distractibility (Wald = 8.22, df = 1, p=0.01) and spatial abilities (Wald = 12.22, df = 1, p<0.0001) were also predictive for ADHD. Conclusion/Discussion: Problem-solving abilities in social processes, auditory short-term memories, visual-spatial abilities, and visual configuration abilities of the children with ADHD were lower than their healthy peers. It was thought that in WISC-R's profile analysis, the categories of freedom from distractibility and spatial abilities could be distinctive in ADHD diagnosis.
Keywords: Adolescent; Attention deficit and hyperactivity disorder; Child; Intelligence Scale for Children-Revised; Mental health; Wechsler; WISC-R